Relação entre níveis séricos de vitamina D e doença hepática gordurosa não alcoólica - Jeniffer Danielle Machado Dutra (2017)
Introduction: Non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease, especially in Western countries. The incidence and severity of NAFLD have been associated with hypovitaminosis D. We aimed to investigate the prevalence of hypovitaminosis D and its association with the severity of the disease and the presence of comorbities. Methods: A cross-sectional study included 139 adults with NAFLD and dosage of 25- hydroxyvitamin D. Inclusion criteria: diagnosis of NAFLD by abdominal ultrasound and/or liver biopsy. Patients with previous or current use of vitamin D supplement were not included. Levels of vitamin D <20 ng/mL were classified as deficiency and between 20-29 ng/mL as insufficiency. Diseases severity was evaluated by NAFLD and BARD scores and histological features according to the NASH Clinical Research Network System. Results: The mean age of the population was 56 ys (range 18-82 ys), most patients were female (83%), 72% had hypertension, 88% were dyslipidemic, 46% had diabetes, 98% had central obesity and 82% had metabolic syndrome. The prevalence of hypovitaminosis D was 78% in the studied population. Most patients (85%) were classified as absent or indeterminate fibrosis by NAFLD score and 24% classified as havinglow risk of developing advanced disease by BARD score. At the cut-off point for vitamin D of 20 ng/mL there was no significant difference in variables studied. At the cut-off point for vitamin D of 30 ng/mL, low levels of vitamin D were associated to the absence of diabetes (p=0.011) and with BARD score (2-4) (p = 0.016). Conclusion: Most patients with NAFLD had hypovitaminosis D and low vitamin D levels were related to the absence of diabetes and disease severity by the BARD score.